23.1k views
1 vote
Quiz 3-3 Parallel and Perpendicular Lines on the Coordinate Plane (Gina Wilson All Things Algebra 2014-2019) need these for a quiz please!

Quiz 3-3 Parallel and Perpendicular Lines on the Coordinate Plane (Gina Wilson All-example-1
Quiz 3-3 Parallel and Perpendicular Lines on the Coordinate Plane (Gina Wilson All-example-1
Quiz 3-3 Parallel and Perpendicular Lines on the Coordinate Plane (Gina Wilson All-example-2
User Poezn
by
5.0k points

2 Answers

6 votes

Answer:

Explanation:

User Kokosing
by
4.7k points
4 votes

Answer:

14.
y = -2x -1

15.
y = -(3)/(4)x +3

16.
y= 4x + 9

17.
y = -(5)/(3)x -2

18.
y= -(2)/(3)x -5

19.
y = 4x -3

20.
y = -3x -7

Explanation:

Solving (14):

Given


(x_1,y_1) = (-7,13)


Slope (m) = -2

Equation in
slope- intercept form is:


y - y_1 = m(x-x_1)

Substitute values for y1, m and x1


y - 13 = -2(x -(-7))


y - 13 = -2(x +7)


y - 13 = -2x -14

Collect Like Terms


y = -2x -14 + 13


y = -2x -1

Solving (15):

Given


(x_1,y_1) = (-4,6)


Slope (m) = -(3)/(4)

Equation in
slope- intercept form is:


y - y_1 = m(x-x_1)

Substitute values for y1, m and x1


y - 6 = -(3)/(4)(x - (-4))


y - 6 = -(3)/(4)(x +4)


y - 6 = -(3)/(4)x -3

Collect Like Terms


y = -(3)/(4)x -3 + 6


y = -(3)/(4)x +3

Solving (16):

Given


(x_1,y_1) = (-5,-11)


(x_2,y_2) = (-2,1)

First, we need to calculate the
slope\ (m)


m = (y_2 - y_1)/(x_2 - x_1)


m = (1 - (-11))/(-2 - (-5))


m = (1 +11)/(-2 +5)


m = (12)/(3)


m = 4

Equation in
slope- intercept form is:


y - y_1 = m(x-x_1)

Substitute values for y1, m and x1


y - (-11) = 4(x -(-5))


y +11 = 4(x+5)


y +11 = 4x+20

Collect Like Terms


y= 4x + 20 - 11


y= 4x + 9

Solving (17):

Given


(x_1,y_1) = (-6,8)


(x_2,y_2) = (3,-7)

First, we need to calculate the
slope\ (m)


m = (y_2 - y_1)/(x_2 - x_1)


m = (-7 - 8)/(3- (-6))


m = (-7 - 8)/(3+6)


m = (-15)/(9)


m = -(5)/(3)

Equation in
slope- intercept form is:


y - y_1 = m(x-x_1)

Substitute values for y1, m and x1


y - 8 = -(5)/(3)(x -(-6))


y - 8 = -(5)/(3)(x +6)


y - 8 = -(5)/(3)x -10

Collect Like Terms


y = -(5)/(3)x -10 + 8


y = -(5)/(3)x -2

18.

Given


(x_1,y_1) = (-6,-1)


y = -(2)/(3)x+1

Since the given point is parallel to the line equation, then the slope of the point is calculated as:


m_1 = m_2

Where
m_2 represents the slope

Going by the format of an equation,
y = mx + b; by comparison


m = -(2)/(3)

and


m_1 = m_2 = -(2)/(3)

Equation in
slope\ intercept\ form is:


y - y_1 = m(x-x_1)

Substitute values for y1, m and x1


y - (-1) = -(2)/(3)(x - (-6))


y +1 = -(2)/(3)(x +6)


y +1 = -(2)/(3)x -4


y= -(2)/(3)x -4 - 1


y= -(2)/(3)x -5

19.

Given


(x_1,y_1) = (-2,-11)


y = -(1)/(4)x+2

Since the given point is parallel to the line equation, then the slope of the point is calculated as:


m_1 = -(1)/(m_2)

Where
m_2 represents the slope

Going by the format of an equation,
y = mx + b; by comparison


m_2 = -(1)/(4)

and


m_1 = -(1)/(m_2)


m_1 = -1/(-1)/(4)


m_1 = -1*(-4)/(1)


m_1 = 4

Equation in
slope\ intercept\ form is:


y - y_1 = m(x-x_1)


(x_1,y_1) = (-2,-11)

Substitute values for y1, m and x1


y - (-11) = 4(x - (-2))


y +11 = 4(x +2)


y +11 = 4x +8

Collect Like Terms


y = 4x + 8 - 11


y = 4x -3

20.

Given


(x_1,y_1) = (-10,3)


(x_2,y_2) = (2,7)

First, we need to calculate the slope of the given points


m = (y_2 - y_1)/(x_2 - x_1)


m = (7 - 3)/(2 - (-10))


m = (7 - 3)/(2 +10)


m = (4)/(12)


m = (1)/(3)

Next, we determine the slope of the perpendicular bisector using:


m_1 = -(1)/(m_2)


m_1 = -1/(1)/(3)


m_1 = -3

Next, is to determine the coordinates of the bisector.

To bisect means to divide into equal parts.

So the coordinates of the bisector is the midpoint of the given points;


Midpoint = [(1)/(2)(x_1+x_2),(1)/(2)(y_1+y_2)]


Midpoint = [(1)/(2)(-10+2),(1)/(2)(3+7)]


Midpoint = [(1)/(2)(-8),(1)/(2)(10)]


Midpoint = (-4,5)

So, the coordinates of the midpoint is:


(x_1,y_1) = (-4,5)

Equation in
slope- intercept form is:


y - y_1 = m(x-x_1)

Substitute values for y1, m and x1:
m_1 = -3 &
(x_1,y_1) = (-4,5)


y - 5 = -3(x - (-4))


y - 5 = -3(x +4)


y - 5 = -3x-12

Collect Like Terms


y = -3x - 12 +5


y = -3x -7

User JIST
by
4.8k points